2018
DOI: 10.1080/09553002.2018.1451006
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of DNA damage and G2 chromosomal radio-sensitivity ex vivo in peripheral blood mononuclear cells with label-free Raman micro-spectroscopy

Abstract: Raman spectroscopy of PBMCs represents a label-free approach for prediction of DNA damage levels for either prospective or retrospective analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 54 publications
(67 reference statements)
0
14
0
Order By: Relevance
“…In contrast, for 0.5 Gy the mean radiation-induced G2 scores exceeded the 90th percentile radiosensitivity cut-off of 152 abs/100 meta for both baseline (167.5 abs/100 meta) and ADT (162.6) compared to the healthy control cohort (122.6 abs/100 meta). It is well reported in the literature that 0.5 Gy IR is the most radiosensitive dose at G2 phase of the cell cycle due to checkpoint inefficacy [ 33 , 34 ], and prostate cancer patients exhibit elevated G2 radiosensitivity compared to healthy control donors at this dose [ 28 , 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, for 0.5 Gy the mean radiation-induced G2 scores exceeded the 90th percentile radiosensitivity cut-off of 152 abs/100 meta for both baseline (167.5 abs/100 meta) and ADT (162.6) compared to the healthy control cohort (122.6 abs/100 meta). It is well reported in the literature that 0.5 Gy IR is the most radiosensitive dose at G2 phase of the cell cycle due to checkpoint inefficacy [ 33 , 34 ], and prostate cancer patients exhibit elevated G2 radiosensitivity compared to healthy control donors at this dose [ 28 , 30 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…This bioassay first described in irradiated cells by Parshad and colleagues [ 24 , 25 ] is now a well-known cytogenetic assay and therefore a biomarker for cellular radiosensitivity [ 26 ]. The assay is well-established and optimised at our own laboratory for predicting cellular radiosensitivity in blood samples obtained from many individuals in various cancer and healthy cohorts [ 27 , 28 , 29 , 30 , 31 ]. Herein, we report the potential of CDKN1, FDXR, SESN1 and PCNA packaged as a 4-gene signature as a potential radiosensitivity biomarker and validated using the G2 chromosomal radiosensitivity profile of individual samples of both the prostate cancer and healthy donor cohort exposed to low doses of IR.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies are devoted at investigating the fixation effects on the Raman spectra of cells [28,29]. In particular, Meade et al showed that a fixation procedure with a low concentration of paraformaldehyde (3.7%) provides the best results and this procedure has been used in many recent studies [19,20,25,26,30,31].…”
Section: Methodsmentioning
confidence: 99%
“…Sophisticated applications of the technique for diagnosis of diseases including cancer [13,23,30,37,52] are now well established while novel applications to monitoring diabetes [39], detection of hyperbilirubinaemia [68], and observation of changes to the cervix during pregnancy [51] have emerged. In addition the sensitivity of Raman spectroscopy to biological effects occuring due to radiation exposure [43], radiotherapy [44] and chemotherapy [49] has also been demobstrated.…”
Section: Application Of Raman Spectroscopy In Identification and Classification Of Immune Cellsmentioning
confidence: 99%